The history of political thought : a very short introduction - Whatmore, Richard (Oxford : Oxford University Press, 2021)
Thinking about politics has tended to be historical in nature because of the comparisons and contrasts that can be drawn between past and present. Different periods in politics have used the past differently. At times political thought can be said to have been drawn directly from the study of history; at others, perhaps including our own time, the relationship is more indirect. This volume explores the core concerns and questions in the field of the history of political thought. Richard Whatmore considers the history of political thought as a branch of political philosophy/political science, and examines the approaches of core theorists such as Reinhart Koselleck, Strauss, Michel Foucault, and the so-called Cambridge School of Quentin Skinner and John Pocock.
Also issued in print: 2021.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 24, 2021).
Keywords: Political science -- Philosophy -- History